Highlighting Intrinsic Objectives Of Bull Race Culture Based on Maqâshid Al-Syarî’ah Kaleidoscope - Ainol Yaqin; Rizqa Ahmadi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2019)
This article is to reveal the intrinsic objectives and values of Bull Race culture. Basically, every culture must contain a purpose forecasted by the first initiator. Therefore, it tries to analyze the culture through Islamic Law by using the theories of ‘urf and maqâshid al-syarîah as the approach. The historical data shows that the intrinsic purpose of the culture is to create prosperity by increasing people’s income, especially in crop production. Besides, this culture also gives additional income to the cow’s livestock. As the result, Bull Race culture really gives great benefit to the society. The dry field becomes fertile and the crop production gets much more successfull. Furthermore, the income of cow also increases significantly because the local cows are healthy and fat with high quality meat. Meanwhile, the noble values from the Bull Race culture are: a. hard working, b. cooperative, c. competitive, d. discipline, e. sportive. Considering the intrinsic objectives and cultural values, it concludes that the culture of Bull Race is not contradictory with the Islamic rules. In fact, it is relevant with the maqasidh al-syari’ah providing that it neither hurts the animals (cows) nor contains gambling and any other immoralities. (Artikel ini adalah untuk mengungkap tujuan dan nilai intrinsik budaya kerapan sapi. Pada dasarnya, tiap budaya harus mengandung tujuan yang diramalkan oleh perintis pertama. Artikel ini mencoba menganalisis budaya kerapan sapi dalam Hukum Islam dengan menggunakan pendekatan teori ‘urf dan maqâshid al-syarîah. Data historis menunjukkan bahwa tujuan intrinsik budaya kerapan sapi adalah untuk menciptakan kemakmuran dengan meningkatkan pendapatan masyarakat, terutama dalam produksi tanaman. Selain itu, budaya ini juga memberikan penghasilan tambahan untuk ternak sapi. Hasilnya, budaya kerapan sapi telah memberi manfaat besar bagi masyarakat. Lahan kering menjadi subur dan produksi tanaman menjadi jauh lebih sukses. Selain itu, pendapatan dari ternak sapi juga meningkat secara signifikan karena sapi lokal sehat dan gemuk dengan daging berkualitas tinggi. Sementara itu, nilai-nilai luhur dari budaya kerapan sapi adalah: a. kerja keras, b. koperasi, c. kompetitif, d. disiplin, e. sportif. Dengan mempertimbangkan tujuan intrinsik dan nilai-nilai budaya, disimpulkan bahwa budaya kerapan sapi tidak bertentangan dengan aturan Islam. Bahkan, relevan dengan maqashid al-syari'ah asalkan tidak menyakiti binatang (sapi) atau mengandung perjudian dan amoralitas lainnya)